Comparison of Intralesional Triamcinolone Acetonide Alone with Intralesional Triamcinolone Acetonide-5-Fluorouracil Combination Injection in Keloid: A Case Report - Mawu, Ferra Olivia; Marlyn Grace Kapantow; Oktavia Reymond L. Sondakh; Elrovita Donata; Paulus Mario Christopher (HM Publisher, 2024)
Keloids are abnormal cutaneous wound healing responses extending beyond the borders of the initial wound, usually appearing pink-purplish to hyperpigmented nodules or plaques with a hard consistency, irregular shape, uneven border, and smooth shiny surface. Most often occur on the chest, shoulder, upper arms, earlobes, and cheeks. This case report aims to compare a case of keloid treated with intralesional triamcinolone acetonide (TAC) alone with intralesional triamcinolone acetonide-5-fluorouracil (TAC + 5-FU) combination injection. A 21-year-old Minahasa male complains of growing pruritic scars in the back area and right and left upper arms since five years ago. Physical examination of the right and left upper arms revealed multiple hyperpigmented nodules and plaques, irregularly shaped, smooth, and shiny surfaces with defined borders and varying sizes. A clinical diagnosis of keloid was made. Treatment was initiated with weekly intralesional TAC alone on the left upper arm vs. intralesional TAC + 5-FU combination injection on the right upper arm. The evaluation was made based on the clinical and modified Vancouver scar scale. One of the most commonly used therapeutic options for keloid is TAC. However, the combination of TAC + 5-FU may be opted for due to its mechanism through the corticosteroid mechanism of action in conjunction with the antimetabolite activity of 5-FU. The combination may yield a more effective and faster outcome with fewer side effects. Intralesional combination TAC + 5-FU injection may be a therapeutic option for keloid with minimal side effects.